Computer Aided Medical Diagnosis Tool to Detect Normal/Abnormal Studies in Digital MR Brain Images - Gutierrez-Caceres, J (2014)
The authors would like to thank to SEDIMED (a medical diagnosis center company in Peru) who supported with a medical images database. This work was partially funded by the Fondos para la Innovacion, Ciencia y Tecnologia (FINCyT-Peru) under contract 142-10-PITEA-FINCyT and CONCYTEC-Peru with STIC-AmSud 2013 under the FERMI project.